Dilapidation works for Mass Rapid Transit (MRT) at Jalan Tun Razak, Kuala Lumpur / Ahmad Hafiz Ahmad Latfi - Ahmad Latfi, Ahmad Hafiz (2018)
Fundamentally, this practical training report is about the dilapidation survey for Mass Rapid Transit System in Kuala Lumpur and my case study building at Menara Kpj Healthcare Berhad, 238, Jalan Tun Razak, because there are also other customers include, Johor Medical Group, Celcom Axiata Bhd and Aegis BPO Malaysia Sdn Bhd, but this dilapidation survey is carried for pre construction, during construction and post construction work which is appointed by MMC-GAMUDA KVMRT Sdn. Bhd. This practical training report have been divided by several part which is the company background, literature review, case study, problem and recommendation and conclusion. In the first chapter, a company background is introduced in detail which is containing the background, location and also logo of company. I also put my organisation of company and several projects that have been done by this company and on-going project. In the second chapter, there is a literature review which I have do some research and review regarding to dilapidation survey itself. This contains the definition of dilapidation survey, purpose, procedures on dilapidation survey, types of defect. There is also a review about by laws and guidelines for dilapidation survey. The following is chapter three, I start with my case study building is the dilapidation survey at Menara Kpj Healthcare Berhad, 238, Jalan Tun Razak, in this chapter I have put the details on the location of our site also dilapidation survey. There is also a scope of work on project. The report that I have done is by area that means, I put the defect by location for example owner unit, external facade, external area and infrastructure. I put the defect analysis to know major or minor defect at my case study building. As the conclusion, by doing a practical training I got knowledge about dilapidation survey, deal an owner and etc. This project I have knew everything on how to solve problem, how to work with professional workers and . I hope that, the report which has been done in followed the requirement that needed and hope to give a satisfactory result to the lecturer